Age- and Weight-Adapted Dose of Prasugrel Versus Standard Dose of Ticagrelor in Patients With Acute Coronary Syndromes : Results From a Randomized Trial - Menichelli, Maurizio; Neumann, Franz-Josef; Ndrepepa, Gjin; Mayer, Katharina; Wöhrle, Jochen; Bernlochner, Isabell; Richardt, Gert; Witzenbichler, Bernhard; Sibbing, Dirk; Gewalt, Senta; Angiolillo, Dominick J; Lahu, Shqipdona; et al. (Annals of internal medicine, 2020)
The efficacy and safety of a reduced dose of prasugrel versus a standard dose of ticagrelor in elderly patients or those with a low body weight presenting with an acute coronary syndrome (ACS) are unknown. To investigate the effect of an age- and weight-adapted dose of prasugrel versus a standard dose of ticagrelor in patients with ACS. (ClinicalTrials.gov: NCT01944800). Prespecified analysis of the multicenter, randomized ISAR-REACT 5 trial. 23 centers in Germany and Italy. 3997 patients with ACS planned for invasive management. Participants were randomly assigned to receive a standard dose of ticagrelor or prasugrel (reduced dose in the elderly or low-weight group and standard dose in the neither elderly nor low-weight group). The efficacy end point was a composite of death, myocardial infarction, or stroke, and the safety end point was bleeding, both at 12 months. In the elderly or low-weight group, the efficacy end point occurred in 12.7% of patients assigned to receive prasugrel and 14.6% of those assigned to receive ticagrelor (hazard ratio [HR], 0.82 [95% CI, 0.60 to 1.14]); in the neither elderly nor low-weight group, the efficacy end point occurred in 4.8% of patients assigned to receive prasugrel and 7.3% of those assigned to receive ticagrelor (HR, 0.65 [CI, 0.48 to 0.88]; for interaction > 0.2). In the elderly or low-weight group, Bleeding Academic Research Consortium type 3 to 5 bleeding occurred in 8.1% of patients assigned to receive prasugrel and 10.6% of those assigned to receive ticagrelor (HR, 0.72 [0.46 to 1.12]), and in 3.7% and 3.8%, respectively, of patients in the neither elderly nor low-weight group (HR, 0.98 [CI, 0.65 to 1.47]; for interaction > 0.2). The study is a subgroup analysis. In elderly or low-weight patients with ACS, a reduced dose of prasugrel compared with the standard dose of ticagrelor is associated with maintained anti-ischemic efficacy while protecting these patients against the excess risk for bleeding. German Center for Cardiovascular Research and Deutsches Herzzentrum München.